New Forces in Old China: An Inevitable Awakening - Brown, Arthur Judson, 1856-1963 (Salt Lake City, UT : Project Gutenberg, 1999)
"New Forces in Old China: An Inevitable Awakening" by Arthur Judson Brown is a historical account written in the early 20th century. The book explores the significant changes underway in China as it becomes influenced by Western trade, politics, and religion, highlighting how these forces are awakening a nation steeped in conservatism and tradition. The author aims to illustrate the monumental transformations occurring in China and their implications for both the country and the wider world. At the start of the book, Brown outlines his intentions for the work, stemming from his experiences and observations during his travels in Asia. He expresses a keen interest in China's vastness and complexity, emphasizing the rich historical context of the region. The opening chapters provide a sweeping overview of China's ancient civilization, its historical ties to various great powers, and the evolving dynamics brought on by foreign influence. Brown sets the stage for a detailed examination of the immense population, economic conditions, and societal changes that characterize China on the cusp of modernity. Through this exploration, he seeks to prompt readers to consider not only the challenges facing China but also the opportunities for transformation that lie ahead. (This is an automatically generated summary.)
Release date is 1999-03-01
Scanned by Charles Keller for Sarah with OmniPage Professional OCR software
Keywords: China -- Politics and government; Missions -- China; China -- Commerce; China -- Foreign relations